Morphological characteristics and phylogenetic analyses revealed five new species (Basidiomycota) from Southwestern China - Ali Yang; Lu Wang; Yongjun Hu; Yingtao Jiang; Guiying Shi; Changlin Zhao (MycoKeys)
In the present study, five new wood-inhabiting fungal species, Conferticium albocremeum (Stereaceae, Russulales), Dendrocorticiopsis luteoalba (Punctulariaceae, Corticiales), Eichleriella biluoxueshanensis (Auriculariaceae, Auriculariales), Gloeohypochnicium yunnanense (Incertae sedis, Russulales), and Punctularia nigrodontea (Punctulariaceae, Corticiales), collected from southern China, are proposed based on a combination of morphological features and phylogenetic evidence. Conferticium albocremeum is characterized by membranaceous and smooth basidiomata with white to cream surface and ellipsoid and verrucose basidiospores (9–11 × 5–7 µm); Dendrocorticiopsis luteoalba is characterized white to buff, membranaceous basidiomata and ellipsoid, thin-walled and smooth basidiospores (7–8 × 4.5–5.5 µm); Eichleriella biluoxueshanensis is characterized by coriaceous and grandinioid basidiomata with buff to cinnamon-buff hymenophore and allantoid, thin-walled basidiospores (13.5–17.5 × 7–9 µm); Gloeohypochnicium yunnanense is characterized by buff to cream, coriaceous and smooth basidiomata and globose, thick-walled and warted basidiospores (10–12 × 10–11.5 µm), and Punctularia nigrodontea is characterized by resupinate to effused-reflexed basidiomata and ellipsoid, thin-walled and smooth basidiospores (8.5–10 × 5–6 µm). Sequences of the internal transcribed spacers (ITS) and the large subunit (nLSU) of the nuclear ribosomal DNA (rDNA) markers of the studied samples were generated. Phylogenetic analyses performed based on the ITS+nLSU rDNA gene regions with the maximum likelihood, maximum parsimony, and Bayesian inference methods revealed that five new species belong to the genera Conferticium, Dendrocorticiopsis, Eichleriella, Gloeohypochnicium, and Punctularia. Descriptions, illustrations, phylogenetic analysis results, and a comparison with closely related taxa of the five new species are provided.